Micro and Nano-plastic particles: What are they and do they effect cardiovascular health? - Banerjee, Indrajit; Robinson, Jared; Sathian, Brijesh; Banerjee, Indraneel; van Teijlingen, Edwin; Roy, Bedanta; Singh, Ashok Pratap (Nepal Journal of Epidemiology, 2024)
Microplastics and Nano-particles ( MNP’s) surround the world around us, and are now not only found within the natural external environment but are also found within our very own internal environment (our tissues). As the world has entered the 21st century and as technology has advanced, the use of plastics predominantly single-use plastics (which are polymeric materials) has rapidly increased to match the global demand and the lifestyle habits as well as creature comforts which are demanded by the modern human being. As time has passed and technology has progressed our understanding of these polymeric compounds and how they interact with our environment and the manner in which they affect our health has improved. It is however noted that our knowledge with regards to these MNP’s still has major gaps and further research is necessitated to understand their full effect on our bodies and natural environment. Micro-plastics and nanoparticles are also known as MNP’s, for a piece of plastic to be considered a “microplastic” it must be less than 5mm in length and a nanoparticle is deemed one if it ranges between 1 to 1000 nanometers in size. The ubiquitous nature of these MNP’s within our environment poses a threat both directly and indirectly to the human race. The majority of these plastic polymeric compounds are produced from petro-chemicals and have innate substances and toxins which contaminate organic living matter. It is clearly evident that MNP’s have a detrimental effect on cardiovascular health, the extent to which is unclear. Further larger scale studies are required and are imperative to providing an improved insight for legislation and governing action.